The Mobius AIRO mobile CT for image‐guided proton therapy: Characterization & commissioning. (24th April 2017) - Oliver, Jasmine A.; Zeidan, Omar A.; Meeks, Sanford L.; Shah, Amish P.; Pukala, Jason; Kelly, Patrick; Ramakrishna, Naren R.; Willoughby, Twyla R.
Abstract: Purpose: The purpose of this study was to characterize the Mobius AIRO Mobile CT System for localization and image‐guided proton therapy. This is the first known application of the AIRO for proton therapy. Methods: Five CT images of a Catphan ® 504 phantom were acquired on the AIRO Mobile CT System, Varian EDGE radiosurgery system cone beam CT (CBCT), Philips Brilliance Big Bore 16 slice CT simulator, and Siemens SOMATOM Definition AS 20 slice CT simulator. DoseLAB software v.6.6 was utilized for image quality analysis. Modulation transfer function, scaling discrepancy, geometric distortion, spatial resolution, overall uniformity, minimum uniformity, contrast, high CNR, and maximum HU deviation were acquired. Low CNR was acquired manually using the CTP515 module. Localization accuracy and CT Dose Index were measured and compared to reported values on each imaging device. For treatment delivery systems (Edge and Mevion), the localization accuracy of the 3D imaging systems were compared to 2D imaging systems on each system. Results: The AIRO spatial resolution was 0.21 lp mm −1 compared with 0.40 lp mm −1 for the Philips CT Simulator, 0.37 lp mm −1 for the Edge CBCT, and 0.35 lp mm −1 for the Siemens CT Simulator. AIRO/Siemens and AIRO/Philips differences exceeded 100% for scaling discrepancy (191.2% and 145.8%). The AIRO exhibited higher dose (>27 mGy) than the Philips CT Simulator. Localization accuracy (based on the MIMI phantom) was 0.6° and 0.5 mm. Localization accuracy (based on Stereophan) demonstrated maximum AIRO‐kV/kV shift differences of 0.1 mm in the x‐direction, 0.1 mm in the y‐direction, and 0.2 mm in the z‐direction. Conclusions: The localization accuracy of AIRO was determined to be within 0.6° and 0.5 mm despite its slightly lower image quality overall compared to other CT imaging systems at our institution. Based on our study, the Mobile AIRO CT system can be utilized accurately and reliably for image‐guided proton therapy.